Menneske – han, hun, den eller det? Genusforenkling og genusændring fra gammeldansk til moderne dansk med sideblik til svensk - Thisted Petersen, Kathrine (Danske Studier, 2019)
In Early and Late Middle Danish (c. 1100–c. 1525), the gender system featured a morphological distinction between the masculine, the feminine, and the neuter. Irrespective of whether nouns denoted humans, animals, things, or abstract categories, the personal pronouns han ‘he’, hun ‘she’, and det ‘it’ were used as anaphoric and cataphoric elements. In Early Modern Danish (c. 1525–c. 1700), however, the masculine and the feminine merged into a common gender represented by the referring pronoun den ‘it’, confining han and hun to nouns denoting humans. This article demonstrates how den was introduced randomly parallel to han and hun until it became part of a new semantically based gender system. Remarkably, during this transitional period including four different kinds of pronominal reference, many nouns changed from one gender to another, presumably because of this new system. In Swedish, a similar development can be observed. By drawing semantic analogies between a couple of parallel Danish and Swedish nouns, I attempt to explain why the original gender changed or did not change, resulting in gender differences between the two languages.